Long‐term follow‐up of unresectable adenoid cystic carcinoma of the trachea and bronchus treated with high‐dose proton beam therapy: A report of two cases - Masatoshi Nakamura; Kayoko Ohnishi; Kensuke Nakazawa; Kei Shimizu; Daigo Miyauchi; Masashi Mizumoto; Kei Nakai; Toshiyuki Okumura; Hideyuki Sakurai (Thoracic Cancer, 2024)
Abstract Adenoid cystic carcinoma (ACC) of the trachea is a rare disease that is slow growing and has a risk of distant metastasis. The standard treatment for ACC of the trachea is surgery, but this tumor is often unresectable. In definitive radiotherapy using photons for unresectable ACC of the trachea, it is sometimes difficult to deliver a sufficient dose to the target without exceeding the tolerable dose to the surrounding normal tissues. Here, we report two cases of ACC of the trachea that received a high dose (74 Gy [relative biological effectiveness]) of proton beam therapy and achieved long‐term survival.